Numerical dataset for analyzing the performance of a highly efficient ultrathin film CdTe solar cell - Rucksana Safa Sultana; Ali Newaz Bahar; Md. Asaduzzaman; Mohammad Maksudur Rahman Bhuiyan; Kawsar Ahmed (Data in Brief, 2017)
The article comprises numerical data of distinct semiconductor materials applied in the sketch of a CdTe absorber based ultrathin film solar cell. Additionally, the contact layer parametric values of the cell have been described also. Therefore, the simulation has been conducted with data related to the hetero-structured (n-ZnO/n-CdS/p-CdTe/p-ZnTe) semiconductor device and a J–V characteristics curve was obtained. The operating conditions have also been recorded. Afterward, the solar cell performance parameters such as open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and efficiency (η) have been investigated and compared with reference cell.